Clinical Study on Electroacupuncture for Post-withdrawal Anxiety-depression Mood in Heroin Addicts - 穆敬平 刘莉 程建明 周立志 敖金波 王军 方伟 胡军 (Journal of acupuncture and tuina science, 2009)
Objective To investigate the intervention effect of electroacupuncture on post-withdrawal anxiety and depression of those with heroin dependence. Method One hundred and twenty heroin dependence cases were randomly allocated into 4 groups, including acupuncture group 1 using Jiaji (Ex-B 2) points and Shenshu (BL 23), acupuncture group 2 using points in the four limbs, simulation and control groups. Then the SAS and SDS changes were observed before the treatment and 4th, 8th and 10th week after. Result At the 4th, 8th and 10th week, the SAS and SDS scores in acupuncture group 1 and 2 showed significant differences with the control group ( P <0.01, P <0.05). There were significant differences between SAS changes in acupuncture group 1 and 2 but there was no significant difference in SDS changes. Conclusion Electroacupuncture can improve the post-withdrawal anxiety and depression in heroin addicts. Jiaji (Ex-B 2) points showed significantly better effects in improving anxiety than points in four limbs but no significant difference in improving depression.